Penggunaan Model Blended Learning terhadap Hasil Belajar di masa Pandemi Covid-19 - Handy Ferdiansyah; Zulkifli N; Rahman Yakub; Agussalim H (Edumaspul: Jurnal Pendidikan, 2021)
This study aims to determine the level of need for the use of the Blended learning model on learning outcomes during the Covid 19 pandemic. This type of research is a quantitative study. Data collection techniques used are observation techniques and questionnaires. The results of this study indicate that the use of the Blended learning model on learning outcomes during the Covid 19 pandemic: (i) illustrates the need for the use of Blended learning models on learning outcomes during the Covid 19 pandemic starting from the government's call for the implementation of Work From Home (ii) the use of Blended learning models for learning outcomes during the Covid 19 pandemic seen from the results of the questionnaires that have been distributed are then processed and analyzed into the Very Practical category.